Efektivitas Penerapan Tanggung Jawab dan Sanksi terhadap Pejabat Pegawai Negeri Sipil dalam Penyalahgunaan Kendaraan Dinas di Kabupaten Sikka - Magdalena Canosa Putri Say; Detji K. E. R. Nuban; Hermawati A. Y. Dai (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Official vehicles are state assets provided to Civil Servants (Pegawai Negeri Sipil/PNS) to support the implementation of official duties and public services. Therefore, their use must comply with applicable regulations and be limited to official purposes. However, the misuse of official vehicles remains a recurring issue in Sikka Regency, involving both civil servants and unauthorized non-civil servants due to weak supervision and inconsistent disciplinary enforcement. This study aims to analyze the effectiveness of the implementation of civil servants’ responsibilities in the use of official vehicles outside official working hours and the effectiveness of disciplinary sanctions imposed for such misuse. This research employed an empirical legal approach using descriptive qualitative analysis. Primary data were collected through interviews with civil servants and relevant officials at the Regional Civil Service and Human Resource Development Agency, the Regional Financial and Asset Management Agency, the Health Office, the Transportation Office, and the Environmental Office of Sikka Regency, while secondary data were obtained through the analysis of legislation and legal literature. The findings indicate that the implementation of moral and administrative responsibilities has not been fully effective, as official vehicles are still used for personal purposes despite clear legal provisions. Likewise, disciplinary sanctions remain ineffective because enforcement is generally limited to verbal and written warnings, while moderate and severe sanctions are rarely imposed. These findings highlight the need to strengthen supervision and ensure consistent enforcement of disciplinary regulations to improve accountability in the use of official vehicles.